A cleaning and efficient approach to improve wet-blue sheepleather quality by enzymatic degreasing. (1st April 2017) - Lyu, Bin; Cheng, Kun; Ma, Jianzhong; Hou, Xueyan; Gao, Dangge; Gao, He; Zhang, Jing; Qi, Yuliang
Abstract: Enzyme is a green, efficient and easily degradable substance. In the present investigation, the papain and 100-c enzyme instead of part of surfactants were used in degreasing process. The results indicated that when wet-blue sheepleather was treated by the enzymatic compound, protein content in the effluent was about 9 times more than that of the non-ionic degreasing agent with less damage to collagen. Moreover, the degreasing rate for enzyme degreasing was 40.1% which was much higher than that of non-ionic degreasing agent. Mechanical properties of the crust leather treated by enzymatic compound were matchable to those treated by non-ionic degreasing agent. Color difference values of the leather indicated that the wet-blue sheepleather was easy to be dyed after being treated by enzymatic compound. The K/S value of the leather treated by enzymatic compound was much higher than that treated by non-ionic degreasing agent. Histological analysis of wet-blues visually showed efficient fat removal by enzymatic compound. Enzymatic compound used in degreasing of greasy wet-blues could improve the leather' quality. Graphical abstract: Highlights: Compound enzyme can remove grease efficiently in the wetting of greasy wet-blue. The use of compound enzyme was good for the dispersion of collagen fibers. The adsorption of dyes was improve after wetting by compound enzyme. Compound enzyme can alternative surfactant in the wetting of wet-blues.